The Profile of Alternative Electrical Energy Literacy (AEEL) among High School Students in West Java and East Java - Irsalina, Fian Rifqi; Amelia, Riski; Suhandi, Andi; Wibowo, Firmanul Catur (Universitas Negeri Semarang, 2025)
This study aims to describe the profile of alternative electrical energy literacy (AEEL) among West Java and East Java high school students, covering cognitive, affective, and behavioral aspects. The research procedure employed a descriptive survey method with a random sample of 237 students, consisting of 130 students from East Java and 107 students from West Java. The instruments used included a knowledge test and a questionnaire on attitudes and behaviors related to alternative electricity energy. The results show that students' affective and behavioral abilities are above average, while their cognitive skills remain below average, with significant differences between the two provinces. Students in West Java understand alternative electricity energy concepts better than students in East Java. Based on these findings, this study is a foundation for schools and policymakers to develop a curriculum focused on alternative electrical energy literacy, aiming to enhance students' understanding of renewable energy sources and prepare the younger generation to face future energy challenges.